How to reduce diagnostic error: ‘neutral zone’ approach - Fanshawe, TR; Vazquez Montes, M (BMJ Publishing Group, 2020)
Many diagnostic tests report only positive or negative diagnoses, as if these results were definitive. Should more tests allow a ‘neutral zone’, corresponding to an uncertain diagnosis?